The Effects of Spatial Planning, Well-Being, and Behavioural Changes During and After the COVID-19 Pandemic - Song, Xinyao; Cao, Mengqiu; Zhai, Keyu; Gao, Xing; Wu, Meiling; Yang, Tianren (Frontiers in Sustainable Cities, 2021)
COVID-19 poses a massive challenge to urban public-health emergency and governance systems. Urban planners and policymakers engaged in spatial planning and management should carefully consider how a “people-oriented” principle can be incorporated into spatial-planning systems to reduce the negative impacts on both cities and people. However, there is limited literature discussing the aforementioned issues, particularly using qualitative methods. Therefore, this research aims to explore the implications of COVID-19 on spatial planning, well-being, and behavioural change using Changchun as a case study. Semi-structured interviews are used to examine the views and insights of 23 participants. Our results show that, first, the shift to home working has changed people's way of life, affected their subjective well-being, and significantly affected spatial planning within cities, placing greater demands on architectural design and community spatial planning. Therefore, additional open public spaces and a more supportive infrastructure are required. Second, it is found that Changchun has not established an effective community-based spatial planning system, something which should have been taken into consideration in the master plan for the future. Third, our findings suggest that being a resilient city is vital for the sustainable development of second-tier cities like Changchun, which is reflected in urban development patterns, disaster prevention, and long-term functional layout, among other aspects. This study contributes to the existing literature on resilient cities, particularly from the perspective of sustainability with regard to resilience to and recovery from major urban crises. In terms of policy implications, planning departments should work with public health and public safety departments to formulate guidelines and management rules in order to improve the spatial planning of cities during periods of extraordinary change and challenge.